Force relaxation of 3/16 inch heavy orthodontic latex elastics used in maxillofacial trauma in simulated jaw fracture situation - Amin Rahpeyma; Saeedeh Khajehahmadi (Wolters Kluwer Medknow Publications, 2014)
Introduction: Orthodontic elastic has been investigated for tooth movement. Study about their use in treatment of jaw fractures is limited. This study is designed to measure force relaxation of 3/16 inch heavy latex orthodontic elastics in jaw fracture treatment simulated conditions. Materials and Methods: This study is designed to study the force relaxation of 45 heavy 3/16 inch orthodontic elastic (American Orthodontist, AO) (4/8 mm internal diameter) were measured using Zwick testing machine (Zwick GmbH & Ulm Germany) in 0, 1, and 14 days of immersion in simulated oral environment. In each of these three occasions, 15 specimens were placed in jigs with metallic pins that inserted 15 mm and 20 mm apart that is equivalent to the normal inter-arch space in a closed mouth position. The jigs were incubated in 37°C and each 24 hours they received 10 thermal cycles of 55°C and 5°C for 30 seconds in a thermocycle. The distribution of the data was evaluated by Klomogrov-Simirnov test and after confirmation of a normal distribution; data was analyzed using analysis of variance (ANOVA). Results: Mean force decay at 15 mm stretch was significantly differ between 0-1 days and 0-14 days (P < 0.05) but was not significantly differ between 1-14 days. The same relations exist for 20 mm stretch. Conclusions: This study creates scientific basis for use of orthodontic elastics in treatment of fractured jaws.